The physiopathologic role of oxidative stress in skeletal muscle. (March 2018) - Scicchitano, Bianca Maria; Pelosi, Laura; Sica, Gigliola; Musarò, Antonio
Highlights: Reactive Oxygen species (ROS) are naturally and constantly formed inside of the organism, as result of cell activity. Different concentrations of ROS can exert opposite effects in skeletal muscle. Oxidative stress is an inducer of muscle aging. Satellite cells are target of oxidative stress. The role of nutrition against muscle oxidative damage is discussed. Abstract: Muscle senescence is a complex mechanism that is usually associated with a decrease in mass, strength and velocity of contraction. This state, known as sarcopenia, is a multifactorial process and it may be the consequence of several events, including accumulation of oxidative stress. The role of oxidative stress in the physiopathology of skeletal muscle is quite complex. Transiently increased levels of oxidative stress might reflect a potentially health promoting process, while an uncontrolled accumulation might have pathological implication. The physiopathological role of oxidative stress on skeletal muscle, its involvement in aging-induced sarcopenia, and potential countermeasures will be discussed.